Recombinant anti-Müllerian hormone in the maturation medium improves the in vitro maturation of human immature (GV) oocytes after controlled ovarian hormonal stimulation - Jure Bedenk; Tadeja Režen; Taja Železnik Ramuta; Nina Jančar; Eda Vrtačnik Bokal; Ksenija Geršak; Irma Virant Klun (BMC, 2022)
Abstract Background In vitro maturation (IVM) of oocytes is a laboratory method that allows the maturation of immature (GV) oocytes retrieved from patients enrolled in the in vitro fertilization (IVF) programme. However, this method is still sparsely researched and used in clinical practice, leading to suboptimal clinical results. Anti-Müllerian hormone (AMH) is an important hormone with known effects on human ovaries, especially on follicles (follicular cells) during folliculogenesis. In contrast, the effect of AMH on the human oocyte itself is unknown. Therefore, we wanted to determine whether human oocytes express AMH receptor 2 (AMHR2) for this hormone. Recombinant AMH was added to the IVM medium to determine whether it affected oocyte maturation. Methods In total, 247 human oocytes (171 immature and 76 mature) were collected from patients enrolled in the intracytoplasmic sperm injection (ICSI) programme who were aged 20 to 43 years and underwent a short antagonist protocol of ovarian stimulation. The expression of AMHR2 protein and AMHR2 gene was analysed in immature and mature oocytes. Additionally, maturation of GV oocytes was performed in vitro in different maturation media with or without added AMH to evaluate the effect of AMH on the oocyte maturation rate. Results Immunocytochemistry and confocal microscopy revealed that AMHR2 protein is expressed in both immature and mature human oocytes. AMHR2 was expressed in a spotted pattern throughout the whole oocyte. The IVM procedure revealed that AMH in maturation medium improved GV oocyte maturation in vitro, as all oocytes were successfully matured in maturation medium containing recombinant AMH only. Furthermore, antagonism between AMH and follicle-stimulating hormone (FSH) during the maturation process was observed, with fewer oocytes maturing when both AMH and FSH were added to the maturation medium. Finally, AMHR2 gene expression was found in immature and in vitro matured oocytes but absent in mature oocytes. Conclusions The positive AMHR2 protein and AMHR2 gene expression in human oocytes shows that AMH could directly act on human oocytes. This was further functionally confirmed by the IVM procedure. These findings suggest the potential clinical application of recombinant AMH to improve IVM of human oocytes in the future.